Evaluation of the projectile's loss of energy in polyester composite reinforced with fique fiber and fabric (2019)
Firearms threat has always been a matter of personal concern, especially to soldiers in armed conflicts as well as police officers and civilians involved with public security. A multilayered armor system (MAS) is intended to personal protection against high kinetic energy ammunition, such as that used in rifles. MAS layers are normally composed of a front ceramic followed by a layer that must show both high impact resistance and low weight. Usually, synthetic fiber fabrics, such as aramid in Kevlar® and ultra-high molecular weight polyethylene (UHMWP) in Dyneema® are commonly used as the second layer. Currently, composites reinforced with natural fibers are also being considered as second MAS layer due to their good performance associated with the advantages of being cheaper and environmentally friendly. The fique is a relatively unknown natural fiber extracted from leaves of a plant native of South American Andes. In the present work, fique fibers and fique fabrics incorporated in polyester composite plates with volume fraction of 10, 20 and 30% were ballistic tested. The calculated projectile loss of energy indicated a relatively large energy dissipation by the composite. The tested specimens were statistically treated by the Weibull analysis and were examined by scanning electron microscopy.